Base promoted direct difunctionalization/cascade cyclization of 1, 6-enynes. Issue 42 (8th May 2018) - Li, Ming; Wang, Cui-Tian; Qiu, Yi-Feng; Zhu, Xin-Yu; Han, Ya-Ping; Xia, Yu; Li, Xue-Song; Liang, Yong-Min
Abstract : A novel base-mediated direct difluoroalkylation of 1, 6-enynes involving a CF2 radical process has been developed. Abstract : A novel base-mediated direct difluoroalkylation of 1, 6-enynes involving a CF2 radical process has been developed. In the absence of metal catalysts, two different difluoroalkylated cyclization products have been synthesized with good functional group applicability and high stereoselectivity. Notably, the properties of a base have been shown to play a crucial role in the generation selectivity of this transformation.